CHANGES IN THE ELASTIC PROPERTIES AND IN THE GRAVITATIONAL FIELD OF ROCKS DUE TO STRONG EARTHQUAKES AND VOLCANOES (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
In this work, the elastic properties of rocks in the focal zones of strong earthquakes and volcanoes, as well as possible changes in gravity, which converge with the arising variations due to such processes, are theoretically calculated and compared.
Keywords: tectonic process; changes in gravity; elastic properties; Jung module; slide module; volcano; earthquake